2016
DOI: 10.1007/s13592-016-0428-8
|View full text |Cite
|
Sign up to set email alerts
|

Structural and temporal dynamics of the bee curtain in the open-nesting honey bee species, Apis florea

Abstract: -Workers of open-nesting honey bee species form a bee curtain to cover the comb and protect it against adverse environmental conditions and predators. We studied different aspects of structural and temporal dynamics of the bee curtain in Apis florea . First, in the course of daily observations, we discovered massed flight activity (MFA) of A. florea colonies similar to that previously described for A. dorsata . The MFAs started with the opening of gaps in the curtain and appearance of chains of bees shortly be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…These results provide first evidence that the age span of nursing behavior in A. florea workers is extended compared to that of A. mellifera workers. This finding corresponds with earlier reports on a delayed onset of foraging in A. florea workers (Dyer and Seeley 1991;Bhagavan et al 2016). Studies in A. mellifera indicate that the workers perform nursing behavior from age of 2 days until the age of about 21 days, and then they start foraging (Ribbands 1952;Lindauer 1952;Seeley 1982;Nowogrodzki 1984;Kolmes 1985;Huang et al 1994;Johnson and Frost 2012).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…These results provide first evidence that the age span of nursing behavior in A. florea workers is extended compared to that of A. mellifera workers. This finding corresponds with earlier reports on a delayed onset of foraging in A. florea workers (Dyer and Seeley 1991;Bhagavan et al 2016). Studies in A. mellifera indicate that the workers perform nursing behavior from age of 2 days until the age of about 21 days, and then they start foraging (Ribbands 1952;Lindauer 1952;Seeley 1982;Nowogrodzki 1984;Kolmes 1985;Huang et al 1994;Johnson and Frost 2012).…”
Section: Discussionsupporting
confidence: 91%
“…Studies in A. mellifera indicate that the workers perform nursing behavior from age of 2 days until the age of about 21 days, and then they start foraging (Ribbands 1952;Lindauer 1952;Seeley 1982;Nowogrodzki 1984;Kolmes 1985;Huang et al 1994;Johnson and Frost 2012). The finding that A. florea workers show an extended period of nursing and a delayed onset of Nursing behavior in Apis florea foraging (Bhagavan et al 2016) compared to A. mellifera workers suggests that their behavioral maturation proceeds more slowly. Dyer and Seeley (1991) showed that open-and cavity-nesting honey bee species differ in many physiological and behavioral traits that are likely function-related and have something to do with differences in metabolic rate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations